Cover Feature: Preparation of a Si/SiO2–Ordered‐Mesoporous‐Carbon Nanocomposite as an Anode for High‐Performance Lithium‐Ion and Sodium‐Ion Batteries (Chem. Eur. J. 19/2018). Issue 19 (16th February 2018) - Zeng, Lingxing; Liu, Renpin; Han, Lei; Luo, Fenqiang; Chen, Xi; Wang, Jianbiao; Qian, Qingrong; Chen, Qinghua; Wei, Mingdeng
Abstract : The Si/SiO2 –ordered‐mesoporous‐carbon (OMC) nanocomposite was initially fabricated through a magnesiothermic reduction strategy using a two‐dimensional bicontinuous mesochannel of SiO2 ‐OMC as a precursor, combined with an NaOH etching process, in which crystal Si/amorphous SiO2 nanoparticles were encapsulated into an OMC matrix. Such unique porous‐crystal‐Si/amorphous‐SiO2 nanoparticles dispersed in an OMC matrix not only mitigate the volume change of the active materials during cycling, but also improve electrical conductivity of Si/SiO2 and facilitate the Li + /Na + diffusion. More information can be found in the Full Paper by Q. Chen, M. Wei, et al. onpage 4841 .